The Concept Of Corruption According To The Perspective Of Islamic Criminal Law - Syarbaini, Ahmad; Lubis, Andi Hakim; Bin Abdulsomad, Muhammat Faosan Dohae (Institute of Education and Social Research, 2024)
Corruption comes from the Latin coruptio and corruptus which means to bribe and corrumpere which means to destroy. Corruption is included in jarîmah. Jarîmah is: